Harmonising measures of knee and hip osteoarthritis in population-based cohort studies: an international study. Issue 7 (July 2018) - Leyland, K.M.; Gates, L.S.; Nevitt, M.; Felson, D.; Bierma-Zeinstra, S.M.; Conaghan, P.G.; Engebretsen, L.; Hochberg, M.; Hunter, D.J.; Jones, G.; Jordan, J.M.; Judge, A.; et al.
Summary: Objective: Population-based osteoarthritis (OA) cohorts provide vital data on risk factors and outcomes of OA, however the methods to define OA vary between cohorts. We aimed to provide recommendations for combining knee and hip OA data in extant and future population cohort studies, in order to facilitate informative individual participant level analyses. Method: International OA experts met to make recommendations on: 1) defining OA by X-ray and/or pain; 2) compare The National Health and Nutrition Examination Survey (NHANES)-type OA pain questions; 3) the comparability of the Western Ontario & McMaster Universities Osteoarthritis Index (WOMAC) scale to NHANES-type OA pain questions; 4) the best radiographic scoring method; 5) the usefulness of other OA outcome measures. Key issues were explored using new analyses in two population-based OA cohorts (Multicenter Osteoarthritis Study; MOST and Osteoarthritis Initiative OAI). Results: OA should be defined by both symptoms and radiographs, with symptoms alone as a secondary definition. Kellgren and Lawrence (K/L) grade ≥2 should be used to define radiographic OA (ROA). The variable wording of pain questions can result in varying prevalence between 41.0% and 75.4%, however questions where the time anchor is similar have high sensitivity and specificity (91.2% and 89.9% respectively). A threshold of 3 on a 0–20 scale (95% CI 2.1, 3.9) in the WOMAC pain subscale demonstrated equivalence with the preferred NHANES-type question. Conclusion: This research provides recommendations, based on expert agreement, for harmonising and combining OA data in existing and future population-based cohorts.